PRAGMATIC LANGUAGE INTERPRETATION AS PROBABILISTIC INFERENCE (Journal of Oriental Studies, 2019)
The main idea of article understands language requires more than the use of fixed conventions and more than decoding combinatorial structure. Instead, comprehends make exquisitely sensitive inferences about what utterances mean given their knowledge of the speaker, language, and context. RSA models provide a principled way to formalize inferences about meaning in context; they have been used to make successful quantitative predictions about human behavior in a variety of different tasks and situations, and they explain why complex phenomena. More generally, they provide a computational frame work for integrating linguistic structure, world knowledge, and context in pragmatic language understanding. Key words: understanding of language, pragmatics, context, rational speech act, cognitive processes.